Clinical diagnosis and management by laboratory methods - Henry, John Bernard (Philadelphia, Pennsylvania : W. B. Saunders Company, 2001)
Contains comprehensive scientific guidance for diagnosis and clinical management as well as disease prevention and health promotion. Focusing on medical and laboratory problem-solving, this edition enables readers to develop an understanding of the order and sequence of lab tests, as well as the interpretation of results.
PART I: The Clinical Laboratory The Clinical Laboratory: Organization, Purpose and Practice Physician Office Laboratories (POLS) Principles of Instrumentation Clinical Laboratory Automation Interpreting Laboratory Results Informatics, Imaging and Interoperability Laboratory Statistics Clinical Laboratory Quality Assurance PART II: Clinical Chemistry Evaluation of Renal Function, Wather, Electrolytes, Acid-Base Balance and Blood Gases Metabolic Intermediates, Inorganic Ions and Biochemical Markers of Bone Metabolism Carbohydrates Lipids and Dyslipoproteinemia Specific Proteins Evaluation of Liver Function and Injury Clinical Enzymology Evaluation of Endocrine Function Toxicology and Therapeutic Drug Monitoring PART III: Urine and Other Body Fluids Basic Examination of Urine Cerebrospinal, Synovial, and Serious Body Fluids Andrology Laboratory and Fertility Assessment Laboratory Management of Assisted Reproductive Technology Laboratory Aspects of Gestation Management Laboratory Diagnosis of Gastrointestinal Tract and Pancreatic Disorders PART IV: Hematology, Coagulation and Transfusion Medicine Basic Examination of Blood Hematopoiesis Erythrocytic Disorders Leukocytic Disorders Blood Platelets Coagulation, Fibrinolysis and Hypercoagulation Immunohematology Transfusion Medicine Hemapheresis Tissue Banking and Progenitor Cell PART V: Immunology and Immunopathy Overview of the Immune System and Immunologic Disorders Immunoassays and Immunochemistry Laboratory Evaluation of the Cellular Immune System Laboratory Evaluation of Immunoglobin Function and Humoral Immunity Complement and Kinins: Mediators of Inflamation Cytokines and Adhesion Molecules HLA: The Major Histocompatability Complex of Man The Major Histocompatibility Complex and Disease Immunodeficiency Disorders Clinical and Laboratory Evaluation of Systemic Rheumatic Diseases Vasculitis Organ Specific Autoimmune Diseases Allergic Diseases Diagnosis and Management of Cancer Using Serologic Tumor Markers PART VI: Medical Microbiology Viral Infections Chlamydial, Rickettsial, and Mycoplasmal Infections Medical Microbiology In Vitro Testing of Antimicrobial Agents Spirochete Infections Mycobacteria Mycotic Diseases Medical Parasitology Molecular Pathology of Infectious Diseases Specimen Collection and Handling for Diagnosis of Infectious Diseases PART VII.: Molecular Pathology An Introduction to Molecular Pathology Molecular Diagnostics: Basic Principles and Techniques Polymerase Chain Reaction (PCR) and Other Amplification Technology Hybridization Array Technology Applications for Cytogenetics in Modern Pathology Establishing a Molecular Diagnostics Laboratory Oncoproteins and Early Tumor Detection Molecular Techniques in the Hematopoietic Neoplasms Molecular Diagnosis of Genetic Diseases Parentage Testing: Use of DNA Polymorphism and Other Genetic Markers Forensic Identity Testing by DNA Analysis.
Includes bibliographical references and index.
Keywords: DIAGNOSIS, LABORATORY